Debt sustainability a global perspective - Schuknecht, Ludger 1962- (Cambridge Elements, 2022)
This study presents the facts, arguments and scenarios around public debt from a global perspective. Especially the largest economies feature record debt and fiscal risks, including from population ageing and financial imbalances. Given low interest rates, there is no imminent problem. But at some point, debt will have to come down. There are four possible scenarios how debt could come down. First, governments could economise and reform. Second, governments could default. Third, governments could erode the real value of debt via inflation and negative real interest rates. However, this scenario cannot continue forever. Policy errors can prompt a loss of confidence, destabilisation and crisis. This fourth scenario last included the largest economies in the 1970s. It would become a major global challenge if it were to happen again in today's interconnected world